Potential Plants Developed With Agroforestry System For Forest Land Rehabilitation In East Java - Indah Rekyani Puspitawati; Anang Susanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Activity the clearing of forest areas and the construction of canals in forest areas, causing a drastic decrease in the forest ground water level and forest depth and causing serious impacts on the ecosystem cycle. the system that will be applied will, of course, be closely related to the interests of the owner of land that expects benefits from the rehabilitation activities carried out. This study aims to provide information about the types of plants that have economic value for the community, according to the extreme nature of forest land, and can be mixed with short-lived plants. Several locations showed survival rates above 75%. There were several types of plants, Albizzia,Tectona, Delbegia, Dipterocarpus, and Gmelina, which were recorded to provide good growth values. The role of the community is needed to the maximum in the efforts to rehabilitate forest land, especially in the area of ​​rights and forest land managed by the community and protected/conservation areas where the community has access to it. Agroforestry has excellent potential to be applied on forest slopes. The application of agroforestry on forest slopes opens new paths for more efficient use of forest slopes with more varied results while considering the aspect of sustainability (conservation). The results of observations made in community gardens and forest lands used by the community and literature review on trials of planting plants for rehabilitation and commodity plants that are economically beneficial to the community, it is known that there are at least ten types of plants.